Declining rates of work‐related overexertion back injuries among union drywall installers in Washington State, 1989–2008: Improved work safety or shifting of care?. Issue 2 (19th August 2013) - Schoenfisch, Ashley L.; Lipscomb, Hester J.; Marshall, Stephen W.; Casteel, Carri; Richardson, David B.; Brookhart, M. Alan; Cameron, Wilfrid
Abstract Introduction Construction workers are at high risk of work‐related musculoskeletal back disorders, and research suggests medical care and costs associated with these conditions may be covered by sources other than workers' compensation (WC). Little is known about the back injury experience and care seeking behavior among drywall installers, a high‐risk workgroup regularly exposed to repetitive activities, awkward postures, and handling heavy building materials. Methods Among a cohort of 24, 830 Washington State union carpenters (1989–2008), including 5, 073 drywall installers, we identified WC claims, visits for health care covered through union‐provided health insurance and time at risk. Rates of work‐related overexertion back injuries (defined using WC claims data) and health care utilization for musculoskeletal back disorders covered by private health insurance were examined and contrasted over time and by worker characteristics, stratified by type of work (drywall installation, other carpentry). Results Drywall installers' work‐related overexertion back injury rates exceeded those of other carpenters (adjusted IRR 1.63, 95% CI 1.48–1.78). For both carpentry groups, rates declined significantly over time. In contrast, rates of private healthcare utilization for musculoskeletal back disorders were similar for drywall installers compared to other carpenters; they increased over time (after the mid‐1990s), with increasing years in the union, and with increasing numbers of work‐related overexertion back injuries. Conclusions Observed declines over time in the rate of work‐related overexertion back injury, as based on WC claims data, is encouraging. However, results add to the growing literature suggesting care for work‐related conditions may be being sought outside of the WC system. Am. J. Ind. Med. 57:184–194, 2014. © 2013 Wiley Periodicals, Inc.